The Effect of GRDP Sector Composition on Economic Growth in the Lake Toba Region - Dany Juhandi; Mangasa Augustinus Sipahutar; Nilam Kemala Odang (Jurnal Ekonomi dan Studi Pembangunan, 2021)
This study aims to analyze the effect of 17 economic sectors on economic growth in the Lake Toba Region (KDT). The data used is secondary data in the form of times series from 2010 to 2019 with panel data analysis using Fixed Model Effect (FEM). It shows a positive and significant influence between mining, energy, information, finance, and health sectors on KDT economic growth, while the other 12 economic sectors have no significant effect. An increase of 1 percent in the mining sector will incline economic growth by 1.41 percent; the energy sector will promote economic growth by 0.48 percent; the information sector will increase economic growth by 0.81 percent; the financial sector will increase economic growth by 0.78 percent; and the health sector will enhance economic growth by 1.10 percent. The government should make policies related to production and investment enhancement so that the income of each economic sector and economic growth in KDT increases. Keywords: Economic growth, Economic sector, Panel dataJEL Classification: C01, C33, O11